Developing a public-private partnership framework for managing the adverse health effects of environmental disaster (a case study of Lake Urmia – Iran). (2nd February 2023) - Gharaee, Hojatolah; Dewey, Rebecca Susan; Gholami, Amir Hossein; Azami-Aghdash, Saber
Abstract: The present study aimed to develop a Public-Private Partnership framework for managing the Adverse Health Effects of Environmental Disasters using the drying lake Urmia case study in Iran. This is a qualitative study with grounded theoretical approach. Data were collected through semi-structured interviews and analyzed using content analysis. To formulate the initial framework, an expert panel was formed. Delphi methodology was used to determine the validity of framework. The most critical infrastructure for private sector participation was designing a legal framework and providing adequate resources and facilities. Pollutant assessment and public education are among the essential areas in which the private sector can participate. To evaluate the performance of the private sector, periodic and short-term reports, and documentation should be used. Payments to the private sector should be for periodic objectives based on performance. Reimbursement should combine service fees, allocation per capita, and performance quality. One of the significant difficulties and challenges in the managing of AHEEDs is lack of resources, poor management and inter-departmental coordination. Policymakers can consider PPP as an effective policy for reducing the AHEEDs. To this end, the framework presented in this study can be used as a guide by national and local authorities and policymakers. HIGHLIGHTS: Decades climate change have caused to different environmental disasters. We conducted 20 semi-structured interviews with experts and came up with a proper insight on understanding different stakeholders in terms of private sector partnership management of adverse health effects of environmental disasters.